Time to Turn to Sustainability: Embracing Terroir Products from Enduring Involvement to Purchase Intention - ZRIBI , Asma; MERSNI , Soumaya (Revue Internationale des Sciences de Gestion, 2026)
The current global situation is both critical and challenging, highlighting the urgent need for sustainable consumption to address these issues. In this context, terroir products have been recognized as a viable solution for achieving sustainability and have gained a notable position among consumers. Enduring involvement with terroir products enables consumers to assess their positive outcomes, fostering a sense of satisfaction, which in turn enhances trust in these products and strengthens purchase intention. Accordingly, this research aims to validate a conceptual framework integrating enduring involvement, satisfaction, trust, and purchase intention toward terroir products. Principal Component Analysis and Structural Equation Modeling were conducted to test the proposed model using survey data collected from 201 Tunisian consumers. The results validate the proposed model and highlight the mediating roles of satisfaction and trust in explaining purchase intention. Specifically, enduring involvement positively influences satisfaction, which subsequently enhances trust and ultimately leads to higher purchase intention. The findings reveal a sequential full mediation, with satisfaction and trust mediating the relationships in the proposed model.